Desenvolvimento de um framework para S-PSS utilizando arquitetura de camadas empresariais - Oliveira, Kaio Vasconcelos de (2021)
Technological development has changed how products and services are created. With the help of robust and autonomous systems, it provided greater agility and flexibility in the production process. In this way, industries have innovated their strategies for implementing new business models where the main focus has been the service, for example, the impact produced by the COVID-19 pandemic showed that in the food sector, the Product-Service Systems (PSS) grew and have become one of the main strategic approaches used. Through a literature research it was noted that the development of an automated framework that can assist designers in creating an S-PSS that encompasses the preparation of products and services at the same time, from its early stages, has become a differential . Thus, the objective of this thesis is to develop a framework for the creation of S-PSS, using a layered architecture, só that the process becomes automatable and só that at all stages there is fluidity and no duplication terms in its development, this takes place through the methodology of information architectures, such as TOGAF. The use of information architecture methods to develop the S-PSS structure presents a great opportunity to carry out its mapping, thus ensuring that the model is adequate to represent real-world situations. The development of this thesis followed the steps proposed by the DSR framework, such as problem identification and motivation, definition of objectives and solution, solution development, solution demonstration and evaluation. Thus, the creation of the FRASE framework was carried out using TOGAF, through the four main architecture layers, which are the business, the data architecture, the application architecture and the technological architecture. In the business architecture, the construction used the BPMN pattern to represent the development stages of the S-PSS. The data architecture was built using the MySQL language containing the entities that represent the necessary information from the previous layer. Application architecture used Bonita to build the relationship between business architecture and data architecture through the creation of portals. Finally, the technological architecture using Bonita provides the use of resources that generate local servers to carry out the application and use the FRASE framework. The evaluation stage compared the PSS development metamodels with the FRASE framework, evaluating the aspects of robustness, ease of use, level of detail and transparency, the FRASE framework achieved the highest score among those analyzed. The framework has the potential to help companies consider all the relevant aspects that need to be analyzed to build an S-PSS.